Prevalence and Risk Factors of High-Risk Population for Stroke: A Population-Based Cross-Sectional Survey in Southwestern China - Yi, Xingyang; Chen, Hong; Wang, Yanfen; Yu, Ming; Luo, Hua; Wang, Chun; Wei, Wei; Chen, Xiaorong; Bao, Shaozhi (Frontiers in Neurology, 2022)
With the aging of the population and the change of lifestyle in China, the prevalence and risk factors of high-risk population for stroke may change. However, few studies performed community-based high risk stroke population survey in China. Hence, we performed this multi-center, cross sectional, community-based survey in Sichuan of southwestern China, according to the China National Stroke Screening Survey (CNSSS) programmeme in 2015. The residents aged ≥ 40 years volunteered to participate in face-to-face survey in 8 communities in Sichuan. The 8 communities were selected using cluster randomization method. Subjects with at least three of the eight stroke related risk factors were classified as high risk population for stroke. Otherwise were classified as low risk population for stroke. Furthermore, 1011 individuals were random selected among low risk population for stroke as controls. A total of 16892 participants, 2369 (14.0%) were high risk population for stroke. After full adjustments, all eight risk factors for stroke were significantly associated with the high risk population for stroke (P < 0.001). The largest contributor was hypertension (population-attributable risk [PAR] 28.4%), followed by physical inactivity [PAR 14.2%], dyslipidemia [PAR 11.2%], overweight/obesity [PAR 9.4%], diabetes [PAR 7.2%], family history [PAR 6.8%], smoking [PAR 5.9%], atrial fibrillation [PAR 3.5%]. Carotid atherosclerosis was more serious in high risk population for stroke than in controls (P < 0.05). The prevalence of the high risk population for stroke was high in southwestern China. Hypertension, physical inactivity and dyslipidemia were stronger contributors for the high risk population for stroke. Individual-level and population-level interventions for these leading risk factors are very important for primary prevention of stroke.